The Study of Learning Organization Models: A Literature Review - Dian Yulia Sari (Journal Research of Social Science, Economics, and Management, 2022)
Peter Senge’s learning organization model, “The Five Building Blocks,” initiated five elements of learning organization, namely “personal mastery, team learning, shared vision, mental models, and systems thinking”. Inspired by this model, several developed learning organization models and the elements are proposed by the scholars in the last two decades in order to preserve the needs of the change world. The aims of this study are to analyse the development of learning organization models and the elements attached to the model. A systematic process of literature review is implemented as the methodology of the study which critically resulted ten journals to be investigated. According to the research, three scholars implemented the five building blocks model from Peter Senge, while the other scholars proposed their studies with developed elements and learning organization models. The characteristics, the readiness, the perception, and the existing conditions of the organizations are several factors that affect the learning organization model. While the differences in the level of how important each element in the learning organization model is also encourages the development of learning organization model itself. Heretofore, the Five Building Blocks model is still very relevant to be used by the scholars and become the basis of learning organization model research in the future.